Natural Jute Fibre-Reinforced Polymer Composite System for Posttensioned Beam Strengthening in Flexure - D. P. Archana; H. N. Jagannatha Reddy; N. Jeevan; R. Prabhakara; M. U. Aswath; Basavaraju Paruti (Advances in Materials Science and Engineering)
Existing structures require repair and strengthening owing to degradation caused by incorrect design and construction, environmental impacts, or structural upgradation to meet new seismic design standards or to correct execution problems that occurred during construction. These strengthening requirements can be satisfied by a variety of strengthening techniques. The creation of a fibre-reinforced polymer (FRP) composite system offers a new design method for the strengthening of existing structures. In this study, posttensioned beams are strengthened by using sustainable materials such as natural jute fibre-reinforced polymer (FRP) composites. The performance of these composite systems in the flexural strengthening of posttensioned beams was used to assess their effectiveness. Consequential result for longitudinal reinforcement throughout the length of the beam for flexural strengthening was evaluated. Flexural performance, crack width, ductility, and load-deflection relationship study of control beams (Scheme A) and retrofitted beams (Schemes B and C) under different wrappings were considered in the investigation. An experimental study depicts that using the full wrapping (FW) technique increases the flexural strength of PSC beams wrapped in JFRP by 23% and, by using the strip wrapping (SW) technique, the flexural strength is increased by 10%. The JFRP composite system of strengthening has shown the highest deformability index and showed that the JFRP material has enormous potential as a structural strengthening material.